Public expenditure economics : an introductory application of welfare economics - Millward, Robert (London McGrraw-Hill, 1971)
This book explores the middleground between pure welfare theory and empirical studies.
osc 13/6/17
Loans
Keywords: Public expenditure; Economics - welfare